Hydrogen diffusion and the effect of hydrogen on structural transformations in binary TiNi based alloys; International Journal of Hydrogen Energy; Vol. 44, iss. 55 - Baturin A. A. Anatoly Anatoljevich; Lotkov A. I. Aleksandr Ivanovich; Grishkov V. N. Viktor Nikolaevich; Rodionov I. S. Ivan Sergeevich; Bordulev Yu. S. Yuri Sergeevich; Kabdylkakov E. A. Erzhan Askarovich (2019, 2019)
Title screen